The management operations of fishing and economic Feasibility gillnet fishermen in the village of pambang Bay, district of bantan, regency of bengkalis, province of Riau - Eri Suwito; Pareng Rengi; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted in July 2012 that took place in the Village District ofBantan Pambang Gulf Bengkalis Riau Province. The method used in this study is asurvey method. The purpose of this study was to determine the feasibility of gillnetfishermen in the village this Pambang bay from the aspects of management of fishingoperations and also from the financial aspect. From the research, that the net operatingmanagement gutters Pambang Bay Village consists of planning, organizing, actuatingand controlling. With the value of Benefit Cost Ratio (BCR) with a value of 1.4. Thissuggests that these efforts be continued. Financial Rate of Return (FRR) is obtainedfrom net fisheries chamfer is 34%. Should be invested into the business. Payback Periodof Cafital (PPC) is 2.9 years, meaning that within a period of 2.9 years net fisheriesgutters able to restore its investment.Keywords: Management of Operations, Feasibility of Economic, Fishing, Gillnet.